Temporal Variation and Statistical Significance Assessment of Seismic b-Value in Iraq and Surroundings (Iraqi National Journal of Earth Science (INJES), 2026)
The b- constant in frequency - magnitude relationship is a crucial factor in seismic studies and seismic hazard assessment. This study aims to evaluate the temporal variation of the b-value and its statistical significance in Iraq and its surroundings. The earthquake catalogue used (1980–2019) is obtained from Onur's (2017) catalogue and updated by Basra University's seismic laboratory. The least squares and the maximum likelihood methods were used to calculate the b-value for two-time windows (five years and one year). The statistical significance of the b-value is evaluated using the Z-test and Utsa's test. Both methods used to calculate the b-value show insignificant differences, indicating no impact of the calculation method on it. The findings showed that the b-value decreases with time. Results of assessing the statistical significance of the b-value for both time windows show statistically significant differences in some years and statistically insignificant differences in others. It was suggested that the statistical significance of the b-value be assessed before it is interpreted.
Keywords: b-value, statistical significance, Temporal variation, Utsa’s test, Z-test